POLA DISTRIBUSI MITOKONDRIA SEL-SEL TROFOBLAS BLASTOSIS MENCIT (Mus Muculus Albinus) DAN PENGARUHNYA TERHADAP KEGAGALAN HATCHING DAN IMPLANTASI - Helmita, Roza; Djuwita, Ita; Purwantara, Bambang (IAIN Batusangkar, 2015)
Implantation is the most critical stage in the establishment of pregnancy. In mammals, it has been estimated that between 25% and 60% of conceptuses are lost before or at the time of implantation. The objectives of this study were to investigate the ability of blastocyst hatching and attachment of trophoblast cells in in vitro, the outgrowth and differentiation of trophoblast cells in in vitro culture of hatched and non hatched blastocyst, the activity of mitochondria NADH-CoQ reductase and the pattern of mitochondrial distribution. Blastocysts were collected from mice cornua utery at day-4 of pregnancy and were divided into 3 groups: blastocysts undergo hatching within 24 hours, 48 hours and non hatching. Embryos were cultured in DMEM medium in 5% CO2 incubator at 37°C for 10 days. The trophoblasts monolayer were processed for Giemsa staining and histochemistry analysis of NADH-tetrazolium reductase activity. The outgrowth of trophoblast cells were measured using eyespiece micrometer. The results showed the ability of blastocyst hatching in in vitro were different. The trophoblast outgrowth diameter of 24 h hatched blastocyst was significantly different with the 48 h hatched and non hatched blastocyst. The activity of NADH-CoQ reductase of 24 h and 48 h hatched blastocysts showed higher intensity than the non hatched blastocysts (P<0,05) and the distribution of mitochondrial in trophoblast cell cytoplasma of 24 h and 48 h hatched blastocyst were homogen around nucleus whereas thoes of non hatched blastocyst were cluster and heterogen. In conclusion, in in vitro study the failure of blastocysts hatching and implantation was due to the failure of outgrowth and differentiation of the trofoblast cells and the impairment of NADH-CoQ reductase activity in complex I mitochondria to produce energy and the pattern of mitochondrial distribution.Key words: mitochondrial distribution, NADH- tetrazolium reductase, trophoblast, implantation